10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Mental health of healthcare workers has been in the spotlight since COVID-19 pandemic, but not enough research is focused on their coping or emotion regulation (ER) strategies. We conducted 15 semi-structured interviews with physicians coming from various specializations and workplace environments and analyzed them via template analysis. Negative emotion triggers were grouped into several bottom-up categories, while the hierarchical organization of ER strategies was informed by the process model of ER. Our findings reveal uncooperative patients as the most significant trigger of negative emotions, but work overload, emotional labor, administrative duties, and relationships with colleagues are also significant. Among ER strategies, we propose psychological distancing as a separate mechanism from cognitive (re)appraisal with its unique utility in helping professions. Strategies across the whole spectrum, including situation selection/modification, attention management, and response modulation, are used by the physicians when performing their job.